2008
DOI: 10.1016/j.jcrs.2008.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lotrafilcon A and omafilcon A bandage contact lenses on visual outcomes after photorefractive keratectomy

Abstract: The N&D lens produced less pain and better postoperative results in terms of haze and BSCVA at 1 month. However, it led to a higher incidence of corneal infiltrates. There was no difference between the lenses in the end result at 12 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 16 publications
0
27
0
2
Order By: Relevance
“…Although the wound healing response equalized beyond this point, superior comfort persisted for a further two days [129,130]. Eyes bandaged with higher transmissibility lenses also achieved significantly better visual acuity and had reduced haze for up to a month [130]. Combining these outcomes with those from studies using lens pairs of more modest differential transmissibility [131][132][133], suggests that similar benefits might accrue down to at least 110 barrers/cm; although inconsistent specification of Dk/t among some of these reports does introduce additional uncertainty.…”
Section: Bandage Lensesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the wound healing response equalized beyond this point, superior comfort persisted for a further two days [129,130]. Eyes bandaged with higher transmissibility lenses also achieved significantly better visual acuity and had reduced haze for up to a month [130]. Combining these outcomes with those from studies using lens pairs of more modest differential transmissibility [131][132][133], suggests that similar benefits might accrue down to at least 110 barrers/cm; although inconsistent specification of Dk/t among some of these reports does introduce additional uncertainty.…”
Section: Bandage Lensesmentioning
confidence: 99%
“…Observation of post-surgical eyes bandaged with either relatively low (35 barrers/cm), or high (175 barrers/cm) transmissibility lenses indicates that the latter are associated with faster corneal re-epithelialisation and reduced pain during the first 48 h of recovery [129]. Although the wound healing response equalized beyond this point, superior comfort persisted for a further two days [129,130]. Eyes bandaged with higher transmissibility lenses also achieved significantly better visual acuity and had reduced haze for up to a month [130].…”
Section: Bandage Lensesmentioning
confidence: 99%
“…These lenses are 5-6 times more oxygen permeable than conventional hydrogel soft contact lenses [19] and have been widely used for extended wear. Studies have shown that silicone hydrogel contact lenses reduce subjective responses more dramatically compared to non-silicone contact lenses and help cornea heal faster [17,20,21]. In addition, no significant difference has been shown between them regarding visual acuity, rate of reepithelialization and contrast sensitivity [15,21].…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, investigators noted that lens oxygen permeability and material affected corneal re-epithelialization and postoperative pain during the early postoperative period after laser refractive surgery. [14][15][16][17] In this study, re-epithelialization at 4 days after epi-LASIK was evaluated by looking for negative fl uorescein staining on slit-lamp examination only. The results seemed to verify complete re-epithelialization in most cases (>85%).…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Several studies have compared lenses of different materials, and other studies have compared the oxygen permeability of different lenses. [14][15][16][17] Epi-LASIK results in the fl attening of the anterior curvature of the cornea, so the base curve of the bandage contact lens may also affect the corneal healing process and visual outcome in the early postoperative period. In the current study, the results of epi-LASIK in eyes treated postoperatively with bandage contact lenses with either an 8.4-mm base curve or an 8.8-mm base curve were compared to determine their effect on corneal healing.…”
mentioning
confidence: 99%